Multiple-pole multilevel diode clamped inverter for permanent magnet synchronous motor drive - Raj, Pinkymol Harikrishna (2015)
A five-level reduced device multilevel inverter is proposed for driving permanent magnet synchronous motor. The proposed multilevel inverter drive consists of lesser number of clamping diodes compared to the conventional five-level diode clamped inverter. An active balancing circuit is used to provide balanced voltages across the four dc-link capacitors to ensure five-level voltage waveform in all operating conditions. The field oriented control of a permanent magnet synchronous motor using space vector modulation technique is implemented to investigate the performance of the proposed inverter drive and results are presented based on simulation done in Matlab/Simulink® and PSIM environment.